Pengaruh Cash Flow dan Leverage terhadap Cash Holding - Ratih Setyo Rini (Universitas Pamulang, 2022)
This study aims to determine the Influence of Cash Flow and Leverage on Cash Holding, an Empirical Study on Manufacturing Companies in the Food and Beverage Sub-sector listed on the Indonesia Stock Exchange in 2015-2020. This type of research is quantitative where to get a sample of 66 data using the purposive sampling method. This study uses secondary data from the annual report on the idx.go.id web which is then processed by panel data regression analysis using EViews 10. The results of this study are simultaneously that cash flow and leverage have a significant effect on cash holding. Partially, cash flow has no effect on cash holding. However, partially leverage has a negative effect on cash holding